DIFFERENCES OF INHIBITION ZONE FOREST PURE HONEY AND CINNAMON (Cinnamomum burmani) AS ANTIBACTERIAL BACTERIAL COMPOUNDS OF MEMBERS OF THE Enterobacteriaceae FAMILY - Eko Naning Sofyanita; Roni Afriansya (Poltekkes Kemenkes Semarang, 2021)
Honey and cinnamon are plant products that have many properties, one of which is used as an antibacterial agent for various diseases. The effectiveness of the two active substances against bacteria in the Enterobacteriaeae family is unclear. The study was conducted to determine the differences in the effectiveness of forest honey and cinnamon in inhibiting the growth of bacteria in the Enterobacteriaceae family. This research method is an experimental study with a combination method of diffusion and wells using samples of the bacteria Klebsiella pneumoniae, Esherichia coli, Salmonella typhi, Serratia marcescens, and Enterobacter cloacae. Forest pure honey and cinnamon were prepared as test solutions with concentrations of 25%, 40%, 55%, 70%, 85% and 100%. The results obtained were the inhibition zone formed on Nutrient Agar Plate (NAP) media, in forest pure honey the inhibition zone formed in S. typhi, E. coli, Klebsiella pneumoniae, Serratia marcescens, and Enterobacter cloacae was greater at 100% concentration, namely 30.5mm, 32.5mm, 38mm, 29.5mm, 26mm, while the 100% concentration of cinnamon showed results, namely 12mm, 10mm, 8.5mm, 11mm, and 11mm. Conclusion is Forest pure honey was more effective at inhibiting bacteria from the Enterobacteriaceae family than cinnamon.